Factors associated with perceived stigma among adolescents with epilepsy attending a tertiary care hospital - Khan, Saira; Khan, Husnea A.; Parvin, Jobaida; Begum, Mosammat S. A.; Debnath, Bithi; Haque, Nazmul; Nasrin, Kamrun N.; Sanom, Sanjana (International Journal of Contemporary Pediatrics, 2026)
Background: Epilepsy is a chronic neurological disorder associated with substantial psychosocial burden and stigma, particularly among adolescents. Understanding the factors contributing to perceived stigma is essential to improve their quality of life. This study aimed to assess the level of perceived stigma and identify associated factors among adolescents with epilepsy. Methods: This cross-sectional study was conducted in the Departments of Paediatric Neurology and Neurology at the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2024 to December 2024. The study population comprised 206 adolescent patients aged 10 to 19 years diagnosed with epilepsy for more than one year and attended the outpatient departments during the study period. Results: The mean age of participants was 14.9±2.6 years, with 64.1% males (male-to-female ratio 1.8:1). Generalized seizures were most common (40.8%). The mean KSSE score was 8.9±4.9, with 33% experiencing high perceived stigma. Commonly reported experiences included feeling treated as outcasts (89.8%), mistreatment (78.2%), and discrimination (71.4%). Factors significantly associated with high stigma included female gender (OR=3.73), family history of epilepsy (OR=3.09), and higher seizure frequency in the last three months (OR=1.14). Disclosure of epilepsy reduced the likelihood of high stigma (OR=0.46). Conclusions: One-third of adolescents with epilepsy experienced high perceived stigma, which was significantly associated with gender, family history, seizure frequency, and disclosure status. Targeted interventions addressing stigma and promoting disclosure may improve psychosocial outcomes in this population.